What is the role of prophylactic cranial irradiation for extensive-stage small-cell lung cancer in an evolving field? - Bang, Andrew; MacRae, Robert M. (Therapeutic Radiology and Oncology, 2019)
The role of prophylactic cranial irradiation (PCI) for extensive-stage small-cell lung cancer (ES-SCLC) has evolved since the publication of two phase III randomized control trials in the past decade. Despite significant evidence demonstrating improvements in survival and rates of developing brain metastasis in the limited-stage setting, there was no clear evidence supporting its use for ES-SCLC until 2007, with the publication of the European Organization for Research and Treatment of Cancer (EORTC) study.